Extracellular matrix metalloproteinases and lipoproteins of high density in young individuals (Revista de Investigaciones Universidad del Quindío, 2012)
Studies in the Quindío and Colombia have reported that HDL is below that levels recognized as normal, howe-ver, the situation is unknown about the apoA-I, MMP2 and MMP9; important variables in the cardiovascular risk (CVR) recognition, especially in young people.Objective: to determine the lipid profile, HDL2 and HDL3 subpopulations, apoA-I, MMP2 and MMP9 serum levels, and establish a relationship between these variables.Methods: The study was conducted at students aged 18 to 29 years. The HDL2 and HDL3 subpopulations were measured by ion precipitation method, the ApoA-I, MMP2 and MMP9 were measured by ELISA.Results: Lipid profile was normal, except for low HDL, despite having normal apoA-I. HDL2 and HDL3 subpo-pulations were found in similar levels (17.31 ± 5.90 and 17.99 ± 6.70 md/dl), respectively, without significant differences between them. MMP2 and MMP9 were 51.05 ± 5.69 ng/ml and 5.29 ± 3.03 ng/ml respectively. Structural analysis found a complex interaction between anthropometric, physiological and biochemical va-riables as: apoA-I, HDL2 and HDL3 subpopulations; between SBP and DBP; between MMP2 and MMP9. Between BMI and apoA-I; corporal weight with HDL2, HDL3, SBP, DBP and MMP2. And between waist circumference with apoA-I, SBP, DBP, MMP2 and MMP9.Conclusions: This study reveals a normal biochemical and physiological state, with interactions between varia-bles, which is compatible with healthy young organisms homeostasis, except fo rthe low total HDL.
Keywords: young; HDL2; HDL3; MMP2; MMP9